BDNF-TrkB Signaling Coupled to nPKCε and cPKCβI Modulate the Phosphorylation of the Exocytotic Protein Munc18-1 During Synaptic Activity at the Neuromuscular Junction - Simó, Anna; Just-Borràs, Laia; Cilleros-Mañé, Víctor; Hurtado, Erica; Nadal, Laura; Tomàs, Marta; Garcia, Neus; Lanuza, Maria A.; Tomàs, Josep (Frontiers in Molecular Neuroscience, 2018)
Munc18-1, a neuron-specific member of the Sec1/Munc18 family, is involved in neurotransmitter release by binding tightly to syntaxin. Munc18-1 is phosphorylated by PKC on Ser-306 and Ser-313 in vitro which reduces the amount of Munc18-1 able to bind syntaxin. We have previously identified that PKC is involved in neurotransmitter release when continuous electrical stimulation imposes a moderate activity on the NMJ and that muscle contraction through TrkB has an important impact on presynaptic PKC isoforms levels, specifically cPKCβI and nPKC. Therefore, the present study was designed to understand how Munc18-1 phosphorylation is affected by (1) synaptic activity at the neuromuscular junction, (2) nPKC and cPKCI isoforms activity, (3) muscle contraction per se and (4) the BDNF/TrkB signaling in a neuromuscular activity-dependent manner. We performed immunohistochemistry and confocal techniques to evidence the presynaptic location of Munc18-1 in the rat diaphragm muscle. To study synaptic activity, we stimulated the phrenic nerve (1 Hz, 30 min) with or without contraction (abolished by µ-conotoxin GIIIB). Specific inhibitory reagents were used to block nPKC and cPKCI activity and to modulate the tropomyosin receptor kinase B (TrkB). Main results obtained from Western blot experiments showed that phosphorylation of Munc18-1 at Ser-313 increases in response to a signaling mechanism initiated by synaptic activity and directly mediated by nPKC. Otherwise, cPKCβI and TrkB activities work together to prevent this synaptic activity–induced Munc18-1 phosphorylation by a negative regulation of cPKCβI over nPKC. Therefore, a balance between the activities of these PKC isoforms could be a relevant cue in the regulation of the exocytotic apparatus. The results also demonstrate that muscle contraction prevents the synaptic activity–induced Munc18-1 phosphorylation through a mechanism that opposes the TrkB/cPKCβI/nPKCsignaling.